DETERMINATION OF PHENOLIC CONTENT AND EVALUATION OF ANTIOXIDANT ACTIVITY OF PROPOLIS FROM ANTIOQUIA (COLOMBIA) - PALOMINO G., Lady R.; GARCÍA P., Carlos M.; GIL G., Jesús H.; ROJANO, Benjamín A.; DURANGO R., Diego L. (Vitae, 2009)
Propolis, a natural product collected by honeybee from exudates of plants, is widely used in traditional medicine due to its known therapeutic properties. In this paper, the quality of ethanol extracts of propolis (EEP) from different regions of Antioquia (Colombia) is compared through the determination of flavonoids and total phenolic compounds content, and thein vitro antioxidant activity, using three assay systems: radical scavenging activity by means of the DPPH• (1-diphenyl-2-picrylhydrazyl) and ABTS•+ (2,2’-azino-bis 3-ethylbenzthiazoline-6-sulfonic acid cation) assays, and ferric reducing antioxidant power (FRAP). Determinations of total phenolic compounds content are found between 22.11 ± 0.54 and 75.22 ± 1.35 mg GAE/g of EEP, and total content of flavonoids between 4.75 ± 0.01 y 34.50 ± 0.07 mg QE/g of EEP. The radical scavenging activity varies from 33.9 ± 9.7 to 324.6 ± 15.0, and from 455.5 ± 7.8 to 1091 ± 17.3 μmol TE/g of EEP (TEAC) in the DPPH and ABTS system, respectively. In the FRAP method, the activity is found between 40.9 ± 13.3 and 338.4 ± 22.4 μmol AAE/g of EEP (AEAC). Results show a positive linear correlation between antioxidant activity and total phenolic content. The antioxidant activity of some propolis indicates its potential role as nutraceutical.